Analisis Penyusunan Modul Ajar Untuk Pembelajaran Bilingual Pada Kurikulum Merdeka di Sekolah Dasar - Munawar, Bunga Muawanah; Humaira, Shafiya Ardya; Naja, Ladya Fairusy; Juwita, Dian; Achmad, Nadia Fajrina; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the characteristics, structure, and principles of compiling bilingual teaching modules in elementary education units in the implementation of the Merdeka Curriculum. The type of research used is a literature review sourced from scientific articles published in 20222025. Data analysis of module components is sourced from English teaching modules for grade 1. The preparation of teaching modules should pay attention to three main components, namely general information components, core components, and appendices. Each component has several parts. Based on the results of the analysis of examples of bilingual teaching modules, it shows that most of the components are in accordance with the standards, although there are still shortcomings in aspects of learning models, glossary preparation, and bibliography format.